Study of concentration of amniotic fluid Alpha-fetal protein in thalassemia fetus - Ling, Yi; Yu, Yan-Hong; Jin, Song; Hu, Chun-Xia; Peng, Wei; Zhang, Hong-Yu; Fu, Huo; Zhang, Ning; Wei, Yan-Xin (Asian Pacific journal of tropical medicine, 2017)
Objective:To test the hypothesis that concentration of amniotic fluid alpha-fetal protein(AFAFP) is increased in thalassemia fetus.Methods:A total of 135 cases of amniocentesis admitted from July 2013 to December 2014 were included in this study.Among them 98 cases of normal fetuses were assigned into control group and 37 cases of thalassemia fetus were included as thalassemia fetus group.Alpha-fetoprotein levels detected by enzyme linked immunosorbent assay and the alpha-fetoprotein concentration were compared between the two groups.There is no significant difference in gestrational age between the two groups.Results:1.AFP concentration in thalassemia fetus group was significantly higher than that of normal control group [(1541.65±734.78) μg/mL vs.(2728.84± 1539.97) μg/mL ],and amniotic fluid AFP concentration was related to fetal thalassemia.2.AFAFP concentration in pureα-thalassemia fetus was higher than that of β thalassemia fetus or mixed αand was not significant.Conclusions:Concentration of a β thalassemia fetus,but the difference mniotic fluid alpha-fetal protein is increased in thalassemia fetus.AFP concentration inα-thalassemia fetus was higher than that of β thalassemia or mixed αand lore β thalassemia fetus but difference was not significance.Further studies are needed to exp the possible correlation between Down syndrome and biochemical markers of Thalassemia.